Antigen-Specific Single B Cell Sorting and Monoclonal Antibody Cloning in Guinea Pigs - Lei, Lin; Tran, Karen; Wang, Yimeng; Steinhardt, James J.; Xiao, Yongli; Chiang, Chi-I; Wyatt, Richard T.; Li, Yuxing (Frontiers in Microbiology, 2019)
Here, we have established an antigen-specific single B cell sorting and monoclonal antibody (mAb) cloning platform for analyzing immunization- or viral infection-elicited antibody response at the clonal level in guinea pigs. We stained the peripheral blood mononuclear cells (PBMCs) from a guinea pig immunized with HIV-1 envelope glycoprotein trimer mimic (BG505 SOSIP), using anti-guinea pig IgG and IgM fluorochrome conjugates, along with fluorochrome-conjugated BG505 SOSIP trimer as antigen (Ag) probe to sort for Ag-specific IgGhi IgMlo B cells at single cell density. We then designed a set of guinea pig immunoglobulin (Ig) gene-specific primers to amplify cDNAs encoding B cell receptor variable regions (V(D)J segments) from the sorted Ag-specific B cells. B cell V(D)J sequences were verified by sequencing and annotated by IgBLAST, followed by cloning into Ig heavy- and light-chain expression vectors containing human IgG1 constant regions and co-transfection into 293F cells to reconstitute full-length antibodies in a guinea pig-human chimeric IgG1 format. Of 88 antigen-specific B cells isolated, we recovered 24 (27%) cells with native-paired heavy and light chains. Furthermore, 85% of the expressed recombinant mAbs bind positively to the antigen probe by enzyme-linked immunosorbent and/or BioLayer Interferometry assays, while 5 mAbs from 4 clonal lineages neutralize the HIV-1 tier 1 virus ZM109. In summary, by coupling Ag-specific single B cell sorting with gene-specific single cell RT-PCR, our method exhibits high efficiency and accuracy, which will facilitate future efforts in isolating mAbs and analyzing B cell responses to infections or immunizations in the guinea pig model.